The Intricate Impression of Tourism, Patent, And Renewable Energy on Environmental Sustainability - Hossain, Md Akter; Acharjee, Sanjoy Kumar; Urbee, Afrida Jinnurain; Kibria, Md Golam; Tahrim, Farian (South Asian Journal of Social Sciences and Humanities, 2024)
The growing global attention to indicating climate conversion and plummeting carbon dioxide (CO2) emanations has spurred researchers to examine the influence of several factors on promoting environmental sustainability. This research examines the intricate role of tourism, patent applications, rent from natural resources, and utilization of renewable power in carbon dioxide secretions in Bangladesh. For this purpose, data has been collected from 1995 to 2019 from World Development Indicators (WDI). Augmented Dickey-Fuller (ADF) and the Phillips-Perron (PP) and the ARDL bound cointegration procedures are employed to determine the existence of stationary data and cointegration among variables respectively. The Autoregressive Distributive Lag (ARDL) procedure is used to consider the effects of the chosen variables on CO2 emissions over the short and long run. VIF test, White's test, and the Breusch-Godfrey test are employed to check multicolinearity, homoscedasticity, and autocorrelation respectively. The research discloses that it is vital to expand the usage of renewable energy sources while simultaneously decreasing natural resource rent by limiting natural resource extraction for a sustainable environment. Although the statistical insignificance of the long-term coefficient of tourism has been observed, the study reveals a negative coefficient for tourism, suggesting the possible efficacy of sustainable tourism practices for mitigating CO2 emissions. The findings also demonstrate the long-term contribution of innovation activities to environmental degradation through the positive coefficient of patent applications. The research results offer significant insights for policymakers and stakeholders involved in the pursuit of a sustainable and ecologically conscious future in Bangladesh.
Keywords: Environmental sustainability; Tourism; Patent; Renewable energy; Natural resource rent; CO2 emissions; Bangladesh; ARDL model